A Study of Isothermal Curing of PMI Using DMA - Jing Zhang; Rui Ye; Jun Zou; Jijun Tang; Hongliang Wang (Advances in Materials Science and Engineering)
The isothermal curing of polymethacrylimide (PMI) is studied through the use of dynamic mechanical analysis (DMA). Based on the growth rate of measured dynamic mechanical property, the relative conversion is defined to investigate the evolution of storage modulus E′ at different curing temperatures. Hsich’s nonequilibrium thermodynamic fluctuation theory, Avrami equation, and isoconversional methods are used to analyze isothermal cure kinetics of PMI. The results show that there are different increase modes of E′ at low temperature range and high temperature range, respectively. In low temperature range, the relative conversion curves include a transitional stage which is found to be strongly frequency-dependent, but this stage is not observed in the relative conversion curve in high temperature range. During the isothermal curing process, the relative evolution of E′ can be described by Hsich’s nonequilibrium thermodynamic fluctuation theory and Avrami equation. Moreover, the values and evolutions of activation energy are different in two temperature ranges, which suggest that the curing mechanism probably has changed.